The Feedback Based Mechanism for Video Streaming Over Multipath Ad Hoc Networks - P Panahi (Journal of Sciences, Islamic Republic of Iran)
Ad hoc networks are multi-hop wireless networks without a pre-installed infrastructure. Such networks are widely used in military applications and in emergency situations as they permit the establishment of a communication network at very short notice with a very low cost. Video is very sensitive for packet loss and wireless ad-hoc networks are error prone due to node mobility and weak links. High quality video transport under ad hoc network is a challenging task due to low bandwidth, high loss rate, unpredictable node mobility, and severe interference characteristics of such kind of network. End to end packet delivery often exhibits low performance due to one hop-by-hop routing failure and misinterpretation to such failures. Multi path routing has been used to increase the robustness for video over ad-hoc networks. The key idea of proposed schema is based on sending video packets over two disjoint paths beside using buffering technique in special nodes of network. In each of every path there is only one node selected as cache node. The main task of these nodes is to realizing different packet types, buffering some of important video packets, reducing forward traffic rate while detecting loss in network and local error management to overcome high loss rate of video packets. Selecting these nodes in network can be as an agreement between video sender and receiver or based on network topological status. The goal of this work is to reduce network end to end delay and increased quality of service over application layer.